Experimental psychology; a manual of laboratory practice - Titchener, Edward Bradford, 1867-1927 (The Macmillan Co.; Macmillan & Co., 1901)
The general purpose with which this book has been written is sufficiently indicated by its title. I have selected a number of the 'classical' experiments of Experimental Psychology, and have tried to present them in such a way that their performance shall have a real disciplinary value for the undergraduate student. Within this general purpose, my aim has been two-fold. I have sought to show, in the first place, that psychology is above the laboratory: that we employ our instruments of precision not for their own sake, but solely because they help us to a refined and more accurate introspection. And secondly, just as in my Outline of Psychology and Primer of Psychology I gave the results of experimentation a prominent place in the psychological system, so here I have treated the selected experiments not as separate exercises, but as points of departure for systematic discussion. (PsycINFO Database Record (c) 2005 APA, all rights reserved)